(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The receipt of alum, which is an initial product to obtain gems, from aluminum containing by products is studied. During alum obtaining process simultaneously methods to isolate practically valuable compounds (e.g. sodium aluminate, aluminum hydroxide, aluminum and ammonium sulfates) have been worked up.